Effects of genetic diversity on physicochemical and functional properties of soybean proteins - Shima Momen; Sanjana Sawant; Benjamin D. Fallen; Audrey L. Girard (Journal of Agriculture and Food Research)
Soybeans are one of the least genetically diverse crops in the U.S., but increasing their diversity is important for making them more resilient and improving protein quality. This study looked at 20 different soybean genotypes to understand how genetic differences affect protein structure and functionality. We found significant variations in particle size (ranging from 243 to 958 nm), zeta potential (−16.5 to −27.1 mV), and surface hydrophobicity (H0 values ranging from 61 × 103 to 140 × 103), which directly influenced how the proteins performed in different applications. SDS-PAGE showed unique patterns for β-conglycinin and glycinin subunits across different genotypes, linking these differences to solubility (60–85 %), hydrophobicity, and overall functionality. Some genotypes had better foaming capacity (up to 58 %) due to balanced protein structures and higher surface hydrophobicity (H0 up to 140 × 103), while others performed poorly, with foaming capacity as low as 35 %, likely due to missing subunits and reduced hydrophobicity (H0 below 65 × 103). Emulsion properties, such as oil and water binding capacity (ranging from 6.01 to 11.67 g oil/g protein and 2.72–6.80 g water/g protein, respectively) and creaming stability, were also influenced by the balance between hydrophobic and hydrophilic properties. These analyses confirmed how protein composition, particularly the balance between hydrophobic and hydrophilic properties, can affect the protein performance in the food system. These findings provide valuable insights for breeding and processing strategies to improve soybean protein quality for various uses.